DENSITY AND NEST-SITE SELECTION OF INVASIVE MYNAS AND STARLINGS IN URBAN AND SUB-URBAN AREAS IN WESTERN SARAWAK, MALAYSIA - Siti Azyyati Nuraini, Mohamed Azizi; Mohamad Fizl Sidq, Ramji; Ng, Wen Teng; Nurul Ashikeen, Ab Razak; Hilda Jelembai, Neilson Ilan; Neilson, Ilan; Mohd Azlan, Jayasilan (Penerbit UMT, 2023)
Urban pest bird species, such as the Asian Glossy Starling, Javan Myna, and Common Myna have been a persistent menace to urban properties. This study compares the population densities of each species within urban and sub-urban areas between Kuching and Kota Samarahan. It was found that Javan Myna and Common Myna populations are concentrated in Pending with population densities of 12.9 ind/ha and 13.3 ind/ha, respectively. The Asian Glossy Starling was found to occupy heavily populated areas in Waterfront and the Universiti Malaysia Sarawak campus, with a population density of 15.0 ind/ha at both sites. We also studied the nesting density and habitat requirements of these species. The highest record of nesting density for the Common Myna (0.8 nests/ha) and Javan Myna (0.7 nests/ha) is in Pending, while the Asian Glossy Starling (2.6 nests/ha) is in Waterfront. The following microhabitat variables influenced the birds’ nest site selection: i) nest distance from garbage bins; ii) nest distance from shrubs and grass; and iii) nest distance from trees. Additionally, the data indicated that the birds had a strong preference for nesting in artificial structures. The Common Myna (25%) chose to nest inside air vents, whereas the Javan Myna (29.63%) and Asian Glossy Starling (51.95%) preferred to nest in holes and cavities.